Non-linear dose-response relationship between uterine artery pulsatility index and risk of preeclampsia in early pregnancy: A secondary analysis based on a nested cohort study - Shaou Wang; Hao Dong (PLoS ONE, 2025)
Background Previous studies have shown that higher uterine artery pulsatility index (UtA-PI) values in early pregnancy have predictive value for the risk of preeclampsia (PE). However, the sensitivity and specificity of this marker remain controversial. This study aims to explore further the association between UtA-PI in early pregnancy and the incidence of preeclampsia. Methods A total of 5000 pregnant women who underwent prenatal examination and delivery at the same hospital were included in this nested cohort study. And the PI values of left and right uterine arteries of the subjects were obtained by transabdominal ultrasound using GE color doppler diagnostic device in early pregnancy (11–13 + 6 weeks), and finally the mean value of both was calculated and recorded as UtA-PI. Among them, 60 pregnant women developed preeclampsia and were randomly divided into a screening group (n = 12) and control group (n = 48) and matched with pregnant women who did not develop preeclampsia during the same period to form a subset for subsequent statistical analysis. A weighted multivariate logistic regression model was used to analyze the association between UtA-PI and PE. Additionally, the non-linear relationship between UtA-PI and the incidence of PE was examined using smooth curve fitting and a generalized additive model. Results After adjusting for other variables, UtA-PI values were positively correlated with the incidence of PE, and the relationship showed a non-linear U-shaped relationship (inflection point 1.83). Conclusion Our study showed a significantly increased risk of PE when UtA-PI exceeded 1.83. This provides a basis for clinicians to identify high-risk pregnant women early and implement timely intervention, which helps to reduce maternal and fetal complications and improve health outcomes.